Innovative Egyptian style sweet and sour table olives - Eid, Mounir M; Mostfa, Dalia M; Ali, Safaa E; Elsorady, Muhammad E (International Journal of Sustainable Agricultural Research, 2025)
Egypt and the EU are the main producers and consumer countries of table olives in the world. The effect of using sugar (3%) in two different treatments (olives treated with NaOH and natural olives) in brine and packaging solutions on the fermentation process was studied. Physical–chemical parameters, including pH, acidity, NaCl content, reducing sugar, and phenol content, were determined for 12 months of storage time, as well as sensory analysis. Results revealed that pH limits were ≤4.0 for treated olives and ≤4.3 for natural olives after 8 months of storage. Moreover, acidity increased with increasing storage time, irrespective of the treatment used. Regarding salt content, values in all treatments were higher than the established limit of the IOC. In addition, data illustrated that treated olives had a lower content of reducing sugars than those of natural table olives. Results also revealed that the phenol content of treated and natural table olives decreased continuously during the fermentation process. The sensory profile regarding hardness, fibrousness, crunchiness, saltiness, acidity, and bitterness was evaluated after 12 months. All treatments were free from abnormal fermentation and defects. The organoleptic analysis of table olives with added sugars showed a unique profile with an increase in acidity and sweetness.